Recent Progress of Carbon Dots for Air Pollutants Detection and Photocatalytic Removal: Synthesis, Modifications, and Applications. Issue 51 (17th October 2022) - Zhao, Jungang; Li, Caiting; Du, Xueyu; Zhu, Youcai; Li, Shanhong; Liu, Xuan; Liang, Caixia; Yu, Qi; Huang, Le; Yang, Kuang
Abstract: Rapid industrialization has inevitably led to serious air pollution problems, thus it is urgent to develop detection and treatment technologies for qualitative and quantitative analysis and efficient removal of harmful pollutants. Notably, the employment of functional nanomaterials, in sensing and photocatalytic technologies, is promising to achieve efficient in situ detection and removal of gaseous pollutants. Among them, carbon dots (CDs) have shown significant potential due to their superior properties, such as controllable structures, easy surface modification, adjustable energy band, and excellent electron‐transfer capacities. Moreover, their environmentally friendly preparation and efficient capture of solar energy provide a green option for sustainably addressing environmental problems. Here, recent advances in the rational design of CDs‐based sensors and photocatalysts are highlighted. An overview of their applications in air pollutants detection and photocatalytic removal is presented, especially the diverse sensing and photocatalytic mechanisms of CDs are discussed. Finally, the challenges and perspectives are also provided, emphasizing the importance of synthetic mechanism investigation and rational design of structures. Abstract : Carbon dots (CDs) have excellent optical and electric properties. They can be synthesized via "top‐down" and "bottom‐up" strategies. Their photoelectronic properties could be tuned by morphology modulation, heteroatom doping, and surface modifications. Based on CDs' outstanding photoelectronic performance, they can be designed as optical and conductor sensors, as well as, photocatalysts for air pollutants detection and removal.